Media and Digital Management - Noam, Eli M. author. aut Link
XVIII, 479 p. 68 illus., 67 illus. in color.
Keywords: Being a successful manager or entrepreneur in the media and digital sector requires creativity, innovation, and performance. It also requires an understanding of the principles and tools of management. Aimed at the college market, this book is a short, foundational volume on media management. It summarizes the major dimensions of a business school curriculum and applies them to the entire media, media-tech, and digital sector. Its chapters cover—in a jargonless, non-technical way—the major functions of management. First, creating a media product: the financing of projects, and the management of technology, HR, production operations, intellectual assets, and government relations. Second, harvesting the product created: market research, marketing, pricing, and distribution. And third, the control loop: media accounting and strategy planning. In the process, this book becomes an indispensable resource for those aiming for a career in the media and digital field, both in startups and established organizations. This book is designed to help those aiming to join the media and digital sector to become creative managers and managerial creatives. It aims to make them more knowledgeable, less blinded by hype, more effective, and more responsible.